2020
DOI: 10.3389/fmicb.2020.00216
|View full text |Cite
|
Sign up to set email alerts
|

eCALIBRATOR: A Comparative Tool to Identify Key Genes and Pathways for Eucalyptus Defense Against Biotic Stressors

Abstract: Many pests and pathogens threaten Eucalyptus plantations. The study of defense responses in this economically important wood and fiber crop enables the discovery of novel pathways and genes, which may be adopted to improve resistance. Various functional genomics experiments have been conducted in Eucalyptus-biotic stress interactions following the availability of the Eucalyptus grandis genome, however, comparisons between these studies were limited largely due to a lack of comparative tools. To this end, we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Respective references to the included studies can be found in Supplementary Tables 1-3 Type of SA marker genes was strongly increased compared to the wild type, and it was suggested that members of the AtNRT2 family might be important for the plant-pathogen interaction (Camanes et al 2012). More recently it was shown that the nrt2.5 mutant displayed similar responses (du Toit et al 2020). Similarly, also NH 4 + transporters such as AtAMT1.1 seem to play an important role for plant resistance (Pastor et al 2014).…”
Section: Availability Of Nitrogen Orchestrates Plant Pathogen Resistancementioning
confidence: 97%
“…Respective references to the included studies can be found in Supplementary Tables 1-3 Type of SA marker genes was strongly increased compared to the wild type, and it was suggested that members of the AtNRT2 family might be important for the plant-pathogen interaction (Camanes et al 2012). More recently it was shown that the nrt2.5 mutant displayed similar responses (du Toit et al 2020). Similarly, also NH 4 + transporters such as AtAMT1.1 seem to play an important role for plant resistance (Pastor et al 2014).…”
Section: Availability Of Nitrogen Orchestrates Plant Pathogen Resistancementioning
confidence: 97%
“…Recently, T - DNA mutants of NRT2.5 showed stronger resistance to Pseudomonas syringae pv. tomato DC3000 inoculation compared to its wild-type counterpart, an indication of NRT2.5 role in plant biotic defense ( Du Toit et al., 2020 ; Devanna et al., 2021 ). These research findings have demonstrated the functional roles of transporters in the plant response to biotic stress, while suggesting safe, innovative, and sustainable means of controlling crop pathogens.Mycorrhizal colonization of rice root also appears to promote the expression of a putative nitrate transporter, OsNPF4.5 .…”
Section: Nitrate Transporters and Environmental Cues: Influence Of En...mentioning
confidence: 99%
“…The Arabidopsis nrt2 double mutant plants ( NRT2.1 and NRT2.2 deficient) grown on reduced N availability displayed reduced susceptibility against the Pseudomonas syringae pv tomato DC3000 ( Pst ) infection (Camañes et al, 2012). Also, the AtNRT2.5 T‐DNA mutant lines exhibit a high level of resistance against P. syringae , indicating the possible role of NRT2.5 in biotic resistance (du Toit et al, 2020). Similarly, Pike et al (2014) reported the inducible nature of VvNPF3.2 gene in V. vinifera and AtNPF3.1 gene in Arabidopsis upon Erysiphe necator attack; these genes code for nitrate and nitrite transporters, respectively.…”
Section: Other Transportersmentioning
confidence: 99%